Comparison of Different Treatment Schedules of Mitomycin C Intravesical Instillation in High-Risk Superficial Bladder Cancer Patients - Chen, Hong-Ray; Kao, Chien-Chang; Tsao, Chih-Wei; Tang, Shou-Hung; En, Meng; Cha, Tai-Lung; Sun, Guang-Huan; Wu, Seng-Tang; Yu, Dah-Shyong (Aktuelle Urologie, 2019)
Objective This study was performed to compare the efficacy of intravesical mitomycin C (MMC) instillation for the prophylaxis of Ta or T1 high-risk nonmuscle invasive bladder cancer (NMIBC) using different schedules. Materials and methods This retrospective cohort study was conducted on 152 patients treated with intravesical MMC from April 2009 to September 2016. The mean follow-up time was 32.67 months. All patients underwent a complete transurethral resection of bladder tumor (TURBT) and postoperative instillation of MMC within 24 h. The patients were divided into 4 treatment groups: Group 1 was followed-up without any maintenance MMC dose treatment; Group 2 received an MMC instillation once per week for the first 8 weeks; Group 3 received an MMC instillation once per week for the first 8 weeks, and once per month for the following 6 months; and Group 4 received an MMC instillation once per week for the first 8 weeks, and once per month for the following 12 months.Results The overall recurrence rate was 27.6 %. Group 1 had a significantly high (p < 0.05) recurrence rate of 50 %, while there was no difference in the recurrence rate between the last 3 schedules (Group 2:15 %; Group 3: 24.1 %; group 4: 27.2 %). Moreover, the recurrence rates of Ta or T1 tumors, and low-grade or high-grade tumors were not statistically different among these patient groups.Conclusion Our comparison of the different schedules of intravesical MMC instillation revealed a significantly higher recurrence rate with one MMC instillation post-TURBT than in patients with a maintenance dose of 8 weeks, 6 months, and 12 months. The time of the MMC maintenance schedule exhibited no significant differences between 8 weeks and 12 months. Thus, we conclude that for T1 or Ta high-risk NMIBC, MMC instillation can be performed once after TURBT, followed by a maintenance treatment once per week for 8 weeks.
Keywords: bladder; Mitomycin C; intravesical instillation; high-risk; urothelial cell carcinoma